Risk Management for the Distribution of Zakat, Infaq, and Shadaqah (ZIS) Funds on the Mentari Scholarship Programme at Zakat Center LAZISMU Gresik - Indah Firdanilla A'yun; Taufiqur Rahman (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
This research analyzes the risks in distributing Zakat, Infaq, and Shadaqah (ZIS) funds in the Mentari Scholarship Program at LAZISMU Gresik and how risk management is applied. This research uses descriptive qualitative methods with triangulation data collection techniques: observation, semi-structured interviews, and documentation. The results showed that there are risks in the distribution of Zakat, Infaq, and Shadaqah (ZIS) funds in the Mentari scholarship program, including (1) Risk of uneven allocation, (2) Risk of lack of coordination between Zakat Management Organisations , (3) Risk of delays in distribution and the risk of findings, namely the risk of administrative delays. The application of risk management in the distribution of Zakat, Infaq, and Shadaqah (ZIS) Scholarship Mentari funds refers to the risk management model in zakat institutions in the BAZNAS and Bank Indonesia books, including the context establishment phase, risk identification, and its impact, risk measurement, risk evaluation, and risk treatment. In addition, risk management applies the principles of priority scale and transparency. The distribution of Zakat, Infaq, and Shadaqah (ZIS) funds must be guided by the SOP for the implementation of pentasyarufan / utilization activities listed in the policy book and LAZISMU management strategic plan for Gresik Regency in 2022.Â